Idiosinkrasi Istri dalam Mencarikan Pasangan Baru Bagi Suami Perspektif Gender - Hawa' Hidayatul Hikmiyah (State Islamic University (UIN) of Sunan Ampel, 2019)
The ideology of a wife in finding a new wife for her husband is considered to be another behavior of most wives in general. Every wife will not want to be polygamy by her husband, but in contrast to the behavior of the wives in the polygamy community is destiny, the majority of wives in the community are competing in achieving God's blessing by finding a new wife for her husband. The wife's behavior is not in the context of pressure from anywhere, which means finding a new wife for the husband purely from his own initiative. With the afterlife orientation, the wives seek, choose and also prepare the husband's marriage with a new wife. There are several motives that influence the idiosyncracy of these wives, including economic, religious, traditional and political motives. In the gender context of a marriage must meet four indicators namely access must be owned by each husband and wife in the family, get a fair role for what the husband and wife do, exercise the same rights and obligations especially in decision making in the family, and benefit from each other in domestic life. In practice polygamy families will have difficulty meeting the four indicators above. Because initially in the condition of the household not always together so that it will affect access, the division of family roles and responsibilities, especially in making all household decisions. Even though there are several motives in polygamy initiated by the wife, it will still have an impact that is vulnerable to family conflicts.